ENTREPRENEURIAL MINDSET AND STRATEGIC PLANNING WORKSHOPS FOR YOUTH STARTUPS - Gesty Ernestivita; Asni Hasanuddin (Adiba Aisha Amira, 2025)
Youth empowerment through entrepreneurial activities is a crucial strategy for addressing unemployment and increasing community economic independence. This study aims to examine in-depth the contribution of entrepreneurial mindset and strategic planning training to supporting the growth and sustainability of startups initiated by the younger generation. Using a literature review method, this research explores various scientific studies, community service reports, and best practices in implementing entrepreneurship training in various regions. The results indicate that training focused on strengthening an entrepreneurial mindset can foster proactive attitudes, risk tolerance, and an innovative spirit in young participants. Meanwhile, strategic planning training equips them with essential skills in setting business goals, managing resources, and developing competitive strategies. In the context of community service, these findings underscore the importance of participatory, contextual, and sustainable training program design to have a long-term impact on developing youth entrepreneurial capacity and improving the welfare of local communities.